High-Tech Sustainable Beauty: Exploring Nanotechnology for the Development of Cosmetics Using Plant and Animal By-Products - Nhani, Gabriela Braga Barros [UNESP]; Di Filippo, Leonardo Delello [UNESP]; de Paula, Geanne Aparecida [UNESP]; Mantovanelli, Vitoria Ribeiro [UNESP]; da Fonseca, Patricia Pereira; Tashiro, Felipe Mota [UNESP]; Monteiro, Diana Coêlho [UNESP]; Fonseca-Santos, Bruno; Duarte, Jonatas L. [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2024)
In a world increasingly focused on eco-conscious living, the cosmetic industry is actively adopting nanotechnology to transform plant and animal by-products into high-value beauty products. This comprehensive review explores the innovative and sustainable approaches for extracting and utilizing bioactive compounds from these by-products. The application of nanocarrier systems is highlighted for their role in enhancing the delivery efficacy and safety of these ingredients in skincare and beauty products. Consumer demand and environmental concerns drive the shift towards natural and sustainable cosmetic products. Traditional cosmetic production often involves significant ecological impacts, prompting the industry to seek greener alternatives. This review addresses the critical need for sustainable beauty solutions that align with global sustainability goals, particularly those outlined in the 2030 Agenda for Sustainable Development. The review provides valuable insights into current trends and future directions in sustainable cosmetics by focusing on nanotechnology and by-products. The review uniquely integrates nanotechnology with sustainability practices in the cosmetic industry. It details the benefits of using nanocarriers to improve the stability, bioavailability, and efficacy of bioactive compounds derived from natural waste. This intersection of high-tech methodologies and sustainability offers a novel perspective on cosmetic innovation. Future research should focus on overcoming the technical, regulatory, and economic challenges of scaling up nanotechnology applications. Investigations should include the development of transparent supply chains, standardization methods for characterizing nanoparticles, and comprehensive lifecycle assessments to ensure environmental safety. Additionally, fostering collaboration between scientific research, industry practices, and consumer education is vital for advancing sustainable practices. This review contributes to the broader discourse on sustainable beauty by presenting a clear pathway for integrating these innovative approaches. It ensures that future cosmetic products meet consumer expectations for efficacy and safety and promote environmental stewardship and a circular economy, ultimately benefiting both the skin and the planet.
Keywords: by-product; circular economy in cosmetics; nanocarrier; sustainable cosmetics